Effect of Chlorella sp. and combinations of selected nutrient sources on growth and yield of onion (Allium cepa L.) - Anushalini, R.; Kajeevan, K.; Gnanavelrajah, N.; Ketheesan, B. (Young Scientists Forum National Science and Technology commission, 2023)
The worldwide increase in human population leads to an increase in the demand for food, which must be supplied by increasing crop production. One of the best options to increase crop production is integrated nutrient management, which incorporates the utilization of different sources of plant nutrients. Compost is an organic component of an integrated nutrient supply system, which enhances soil health, improves macro and micronutrient availability, and increases crop productivity [1]. Biofertilizers are also a key component in integrated nutrient management. Chlorella is green algae rich in macro and micronutrients [2], however, a huge amount of water and nutrients are essential for cultivating Chlorella. The effluent produced in the dairy industry contains a high amount of nutrients and therefore could be used as a growth medium for the cultivation of Chlorella. In this context, this study was conducted to check the potential of cultivating Chlorella sp. in dairy industry wastewater and to find the potential effect of different nutrient sources (inorganic, compost, and Chlorella) and their combinations on the growth and yield of onion (Allium cepa L.).
Keywords: Onion; Chlorella sp